Mu opioid receptor localization in the basolateral amygdala: An ultrastructural analysis. (10th September 2015) - Zhang, J.; Muller, J.F.; McDonald, A.J.
Highlights: MOR-ir was seen in the Golgi apparatus of pyramidal neurons (PNs) and interneurons. Many dendritic shafts and spines were MOR+. Diffuse MOR-ir was seen in the perikarya and dendritic shafts of some interneurons. MOR+ axon terminals forming asymmetrical synapses mainly contacted spines. MOR+ terminals forming symmetrical synapses contacted PN somata and dendrites. Abstract: Receptor binding studies have shown that the density of mu opioid receptors (MORs) in the basolateral amygdala is among the highest in the brain. Activation of these receptors in the basolateral amygdala is critical for stress-induced analgesia, memory consolidation of aversive events, and stress adaptation. Despite the importance of MORs in these stress-related functions, little is known about the neural circuits that are modulated by amygdalar MORs. In the present investigation light and electron microscopy combined with immunohistochemistry was used to study the expression of MORs in the anterior basolateral nucleus (BLa). At the light microscopic level, light to moderate MOR-immunoreactivity (MOR-ir) was observed in a small number of cell bodies of nonpyramidal interneurons and in a small number of processes and puncta in the neuropil. At the electron microscopic level most MOR-ir was observed in dendritic shafts, dendritic spines, and axon terminals. MOR-ir was also observed in the Golgi apparatus of the cell bodies of pyramidal neurons (PNs) and interneurons. Some of the MOR-positive (MOR+) dendrites were spiny, suggesting that they belonged to PNs, while others received multiple asymmetrical synapses typical of interneurons. The great majority of MOR+ axon terminals (80%) that formed synapses made asymmetrical (excitatory) synapses; their main targets were spines, including some that were MOR+. The main targets of symmetrical (inhibitory and/or neuromodulatory) synapses were dendritic shafts, many of which were MOR+, but some of these terminals formed synapses with somata or spines. All of our observations were consistent with the few electrophysiological studies which have been performed on MOR activation in the basolateral amygdala. Collectively, these findings suggest that MORs may be important for filtering out weak excitatory inputs to PNs, allowing only strong inputs or synchronous inputs to influence pyramidal neuronal firing.